Renaissance Go-Betweens: cultural exchange in early modern Europe - Höfele, Andreas; Koppenfels, Werner von (Spectrum Literaturwissenschaft, 2005)
The Renaissance translator as go-between / Peter Burke -- Inglese italianato-Italiano anglizzato : John Florio / Manfred Pfister -- Ash Wednesday in Westminster : Giordano Bruno meets Elizabethan England / Werner von Koppenfels -- De Witt, van Buchell, the wooden O, and the yellow M / Paul Frassen -- John Dee as cultural, scientific, apocalyptic go-between / Gy(c)œrgy E. Sz(c)œnyi -- John Wolfe and the impact of exemplary go-betweens on early modern print culture / Sonia Massai -- Hybrids : learning from a gilded silver beaker (Antwerp, c. 1530) / Carlo Ginzburg -- British cultural history and church history for the continent : John Bale's Summarium (1548) and Catalogus (1557-59) / Herbert Grabes -- Machiavellian dissimulation and allegory : the writings of Roger Ascham and Sir Philip Sidney / John Roe -- Moses as go-between : John Spencer's theory of religious translation / Jan Assmann -- Another country : Marlowe and the go-between / Richard Wilson -- Spirits, ghosts, demons in Shakespeare and Milton / Aleida Assmann -- A membrane has broken : returning from the dead in The Spanish tragedy / Alexander Leggatt -- The words of Mercury : Shakespeare's love ambassadors / Fran(c)ʹois Laroque -- Incising Venice : the violence of cultural incorporation in The merchant of Venice / Philippa Berry -- Iago the essayist : Florio between Montaigne and Shakespeare / Catherine Belsey